Endophytic Streptomyces SUK10: its molecular characteristic and bioactivity against malaria parasite - Baba, Mohd Shukri; Abu Hassan, Zainal Abidin; Latip, Jalifah; Mohamad Zin, Noraziah; Herron, Paul R.; Edrada-Ebel, RuAngelie
It has been known that Streptomyces is the mains source for antibiotics. The present study found that the crude extract obtained from Streptomyces SUK10 living endophytically in Shorea ovalis tree has antimalarial activity against Plasmodium berghei strain PZZ1/100. Using validated surface sterilization and isolation method, Streptomyces SUK10 was isolated from the bark of Shorea ovalis by and cultured on the isolation agar. With spiral spore chain, microscopically, this strain has substrate mycelium in brownish yellow and aerial mycelium in whitish grey, other than yellow dissolved pigment. As showed in early molecular tests, the 23S rRNA sequence of Streptomyces SUK10 was 96% identical to Streptomyces hygroscopicus, the outstanding producer of Hygromycin B antibiotic. In early phase of antimalarial screening, the secondary metabolites from three different strains of endophytic Streptomyces isolated from three different trees were in-vivo tested on the mice ICR strain against P. berghei strain PZZ1/100. These were done by implementing the four days (4D) suppression test using their own ethyl acetate-crude extract at four different concentrations: 50, 100, 200 and 400 µg/kg body weight (bw). Upon obtaining significant results (p ≤ 0.05), ethyl acetate-SUK10 crude extract were screened for fully anti-malarial activity at five different narrower concentration range 5, 10, 50, 100 and 200 µg/kg bw. There was a positive relationship between the survival of the infected mice group treated with 50 µg/kg body weight of ethyl acetate-SUK10 crude extract and its ability to inhibit the parasites growth. Considering quinine hydrochloride at 10 mg/kg bw and 0.9% normal saline as positive and negative control respectively, the parasite inhibition percentage for this group at certain concentration showed more than 70% and 50% of this mice members (n=3) were also able to survive more than 90 days after the infection with the parasite. Nevertheless, Indole-3-lactic acid (C11H11NO3) was isolated from the anti-trypanosomal active fraction while Gancidin W or Maculosin 6 (L-leucyl-L-prolyl lactam, C11H18N2O2) was the major compound found from SUK 10 crude extract. Gancidin W has been previously reported to be anti-parasitic which we are still yet to be tested for anti-malarial activity and its cytotoxicity. These promising findings contribute to the medicinal and pharmaceutical field for future antimalarial treatment.